MEASUREMENT AND INTERPRETATION OF THE IMPACT OF SOME MACROECECONOMIC VARIABLES ON THE PERFORMANCE OF AGRICULTURAL SECTOR IN SELECTED DEVELOPING COUNTRIES - Alaa M. Abdullah (Mesopotamia Journal of Agriculture)
Are macroeconomic variables one means by which measure the performance of economic sectors including the agricultural sector, because they are interested in studying how they are through to reach the level equilibrium of the sector, through the knowledge of the changes that you get the rates of growth and the problems faced over time, And that part of the cause of this is due to the difference in the performance of the agricultural policy makers in these economies to counter these influences that contribute to the effects of directly or indirectly in the performance of its agricultural sector, as well as the effects of different variables that contribute to the macroeconomic performance of the agricultural problem arose here, Came the importance of research in the economic development of developing countries in which the role of agriculture in large macroeconomic disrupted if agriculture is neglected and deprived of resources or subjected to prejudice because of the use of policies that negatively impact on producer incentives While research aimed at identifying and measuring the impact of macroeconomic variables on the performance of the agricultural sector in a number of developing countries during the period (1980-2007), depending on the hypothesis that macroeconomic variables have different impacts in the performance of the agricultural sector in a number of developing countries, according to the nature of the structures economic and efficiency of their policy in dealing with these variable, In order to prove this hypothesis has been selected number of developing countries that included Egypt, Morocco, Turkey, Indonesia, Thailand, Malaysia and Tunisia, which has been the use of model regression combination (Pooled Regression), which measures the effect of economic variables on growth rate of Vary from one country to another, and during the analysis was the conclusion that the independent variables, namely inflation and the exchange rate and the average per capita GDP and economic openness agricultural and government spending and programs of the International Monetary Fund and the interest rate) with different impacts (positive and negative) in the rate of the growth of agricultural output (variable-based) in each country of the sample as well as in meta-analysis of selected countries .